Dr. Fernando Brito — Deep Plane Facelift — Abuja - Brito, Fernando (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Fernando Brito, practicing in Abuja, Nigeria. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003267; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; nigeria; abuja